Optimization of mechanical properties of geopolymer mortar based on Class C fly ash and silica fume: A Taguchi method approach - Hasan Altawil; Murat Olgun (Case Studies in Construction Materials)
This study examines the mechanical properties of Class C fly ash-based geopolymer mortar to optimize its use. Using Taguchi's experimental design methodology, compressive and flexural strength tests were conducted to determine the ideal mix ratios. An L16 orthogonal array with five factors and four levels was used to assess the effects of sodium hydroxide concentration (10, 12, 14, and 16 M), alkaline solution-to-binder ratio, sodium silicate to sodium hydroxide ratio, water to geopolymer solids ratio, and aggregate percentage. Samples were cured at room temperature for 28 days. Results showed that the highest compressive strength (20.52 MPa) was achieved with alkaline solution-to-binder ratio = 0.3, water-to-geopolymer solids ratio = 0.35, sodium silicate-to sodium hydroxide ratio = 1.75, and aggregate percentage = 0.60, while the lowest (2.64 MPa) occurred with alkaline solution-to-binder ratio = 0.3, water to geopolymer solids ratio = 0.55, sodium silicate to sodium hydroxide ratio = 2.5, and aggregate percentage = 0.65. Similarly, the highest flexural strength (4.69 MPa) was noted with alkaline solution-to-binder ratio = 0.3, water-to-geopolymer solids ratio = 0.35, sodium silicate to sodium hydroxide ratio = 1.75, and aggregate percentage = 0.60, and the lowest (0.57 MPa) with alkaline solution-to-binder ratio = 0.3, water to geopolymer solids ratio = 0.55, sodium silicate to sodium hydroxide ratio = 2.5, and aggregate percentage = 0.65. The optimal parameters for maximum compressive strength were water-to-geopolymer solids ratio = 0.35, molarity = 10 M, alkaline solution-to-binder ratio = 0.40, sodium silicate to sodium hydroxide ratio = 2.0, and aggregate percentage = 0.70. For flexural strength, the optimal levels were water to geopolymer solids ratio = 0.35, molarity = 10 M, alkaline solution-to-binder ratio = 0.40, sodium silicate to sodium hydroxide ratio = 1.75, and aggregate percentage = 0.70.